2015
DOI: 10.1016/j.jclepro.2014.12.094
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of water footprint of the iron and steel industry: a case study in Eastern China

Abstract: 1China is the largest producer of iron and steel in the world. This heavy industry is 2 characterized by significant water consumption and numerous water-related 3 hazards. In this study, we propose the use of water footprint instead of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(56 citation statements)
references
References 28 publications
1
49
0
6
Order By: Relevance
“…Water and energy are the crucial constituents of iron and steel industry, where energy and water sustainability are inextricably intertwined [111]. Large amount of water is used for direct and indirect cooling, gas cleaning, scale breaking and washing operations including waste gas cleaning with scrubbers during iron and steel production processes [112].…”
Section: Water Use and Waste Water Management In Steel Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…Water and energy are the crucial constituents of iron and steel industry, where energy and water sustainability are inextricably intertwined [111]. Large amount of water is used for direct and indirect cooling, gas cleaning, scale breaking and washing operations including waste gas cleaning with scrubbers during iron and steel production processes [112].…”
Section: Water Use and Waste Water Management In Steel Industrymentioning
confidence: 99%
“…He stated that recycling the drainage water is a practical and helpful method to reduce CO 2 emission by improving the performance of the system. Gu et al [111] proposed a water footprint (direct and virtual) calculation model by analyzing the characteristics of the iron and steel industry from a life cycle assessment perspective. Besides, Guo and Fu [115] showed that by adopting coke dry quenching technology can enable to save 10% of water around 0.38 t of water for every tone of coke.…”
Section: Water Use and Waste Water Management In Steel Industrymentioning
confidence: 99%
“…This indicator has been implemented for the iron and steel industry instead of conventional indicators, such as FWC per tonne of steel and WC per tonne of steel. This can lead to the improvement of water efficiency, and, consequently, to a lower environmental impact of the production (Gu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The significant difference between them is that the WFN approach mainly focuses on water management while the LCA approach mainly focuses on the sustainability of products [30]. LCA-based WFs can be utilized to evaluate the aquatic environmental effects of products or businesses during the whole life cycle, including raw material acquisition, supply chain, manufacturing, carriage, usage, and waste treatment [38][39][40]. WFN emphasizes the effective and sustainable allocation and use of fresh water from a product, consumption, industry, and geographical perspective [41][42][43][44][45][46].…”
Section: Water Footprintmentioning
confidence: 99%